2014
DOI: 10.1039/c3fo60657k
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulating effects of casein-derived peptides QEPVL and QEPV on lymphocytes in vitro and in vivo

Abstract: Lymphocytes serve an important function in mediating specific immune responses. When the body is stimulated by internal or external antigens, activated lymphocytes proliferate to clear pathogens by secreting antibodies or cytokines. Some bioactive peptides were isolated from fermented milk in previous studies. One of the peptides, Gln-Glu-Pro-Val-Leu (QEPVL), was synthesized and used in this experiment. Results show that QEPVL can significantly activate lymphocytes both in vitro and in vivo. QEPVL can also inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 27 publications
0
26
1
Order By: Relevance
“…In an intestinal immune system, moderate pro‐inflammatory cytokines could play a beneficial role in host as a defence against intracellular pathogens, while the overproduction might result in pathological conditions and immune function decline (Barilli et al ., ; Jiehui et al ., ); therefore, the introduction of anti‐inflammatory cytokines is essential for maintaining a homoeostasis. The results in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In an intestinal immune system, moderate pro‐inflammatory cytokines could play a beneficial role in host as a defence against intracellular pathogens, while the overproduction might result in pathological conditions and immune function decline (Barilli et al ., ; Jiehui et al ., ); therefore, the introduction of anti‐inflammatory cytokines is essential for maintaining a homoeostasis. The results in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, both these peptides were also shown to attenuate atherosclerosis development in apolipoprotein in E‐deficient mice (Nakamura et al, ). Another milk casein‐derived peptide, QEPV (Gln‐Glu‐Pro‐Val), was shown to inhibit the release of nitric oxide (NO) while increased the production of anti‐inflammatory mediators IL‐4 and IL‐10 (Jiehui et al, ). High hydrostatic pressure treated whey protein hydrolysates have also been shown to have anti‐inflammatory effects on intestinal epithelial and respiratory cells (Piccolomini, Iskandar, Lands & Kubow, ), although the peptides responsible for the activity has not been identified yet from the crude hydrolysate.…”
Section: Food‐derived Anti‐inflammatory Peptidesmentioning
confidence: 99%
“…Amongst them, peptides with immunomodulatory ability had been focused on by more and more researchers. Casein-derived peptides QEPVL and QEPV could significantly increase mice lymphocyte proliferation rate and cAMP levels in vitro and also inhibited LPS-induced inflammation by regulating nitric oxide release and the production of the many cytokines in vivo (Zhou et al, 2014). Novel peptides isolated and characterized from the chicken bursa of Fabricius promoted the development of mice B cell and enhanced the production of specific Avian Influenza Virus antibody and cytokines, T-cell immunophenotyping at reachable concentrations (Liu et al, 2013).…”
Section: Introductionmentioning
confidence: 98%